Collective impact of chronic medical conditions and poverty on perinatal mental illness: population-based cohort study. Issue 2 (2nd November 2019) - Faulkner, Mary-Rose; Barker, Lucy C.; Vigod, Simone N.; Dennis, Cindy-Lee; Brown, Hilary K
Abstract : Background: Chronic medical conditions (CMCs) and poverty commonly co-occur and, while both have been shown to independently increase the risk of perinatal mental illness, their collective impact has not been examined. Methods: This population-based study included 853 433 Ontario (Canada) women with a singleton live birth and no recent mental healthcare. CMCs were identified using validated algorithms and disease registries, and poverty was ascertained using neighbourhood income quintile. Perinatal mental illness was defined as a healthcare encounter for a mental health or substance use disorder in pregnancy or the first year postpartum. Modified Poisson regression was used to test the independent impacts of CMC and poverty on perinatal mental illness risk, adjusted for covariates, and additive interaction between the two exposures was assessed using the relative excess risk due to interaction (RERI) and synergy index (SI). Results: CMC and poverty were each independently associated with increased risk of perinatal mental illness (CMC vs no CMC exposure: 19.8% vs 15.6%, adjusted relative risk (aRR) 1.21, 95% CI (CI) 1.20 to 1.23; poverty vs no poverty exposure: 16.7% vs 15.5%, aRR 1.06, 95% CI 1.05 to 1.07). However, measures of additive interaction for the collective impact of both exposures on perinatal mental illness risk were not statistically significant (RERI 0.02, 95% CI −0.01 to 0.06; SI 1.09, 95% CI 0.95 to 1.24). Conclusion: CMC and poverty are independent risk factors for perinatal mental illness and should be assessed as part of a comprehensive management programme that includes prevention strategies and effective screening and treatment pathways.